2018
DOI: 10.1371/journal.pone.0205536
|View full text |Cite
|
Sign up to set email alerts
|

ALDH1A1 expression is associated with poor differentiation, ‘right-sidedness’ and poor survival in human colorectal cancer

Abstract: BackgroundAldehyde dehydrogenase 1A1 (ALDH1A1) encodes an enzyme that oxidizes aldehydes to their corresponding carboxylic acids. In colorectal cancer ALDH1A1 marks cancer stem cells and plays putative roles in tumor progression and drug resistance. However, the potential value of ALDH1A1 as a diagnostic marker or target for therapy remains unclear. Here, we have analyzed ALDH1A1 mRNA and protein levels in relation to clinical, histopathological and molecular tumor features in large series of human colorectal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…ALDH1A1 plays a major role in the progression of several solid tumours. 6,[29][30][31] Ginestier et al 4 have reported that ALDH1A1 is a specific marker for isolated BCSC. Furthermore, ALDH1A1 has been reported as being a marker for CSC in solid cancers such as lung 13 and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1A1 plays a major role in the progression of several solid tumours. 6,[29][30][31] Ginestier et al 4 have reported that ALDH1A1 is a specific marker for isolated BCSC. Furthermore, ALDH1A1 has been reported as being a marker for CSC in solid cancers such as lung 13 and colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…List of well-validated biomarkers for colon cancer stem cells from the validated experimental setup (along with a review for more reference and importance) retrieved from the CellMarker database [39] and populated thereafter (for the ease of reading). The gene M31994 encodes Aldehyde dehydrogenase 1A1 (ALDH1A1), which catalyzes aldehydes to their corresponding carboxylic acids through the oxidation process [44]. It has also been enunciated that a considerable amount of ALDH1A1 enrichment occurs in colon cancer [45,46].…”
Section: Resultsmentioning
confidence: 99%
“…The gene M31994 encodes Aldehyde dehydrogenase 1A1 (ALDH1A1), which catalyzes aldehydes to their corresponding carboxylic acids through the oxidation process [ 44 ]. It has also been enunciated that a considerable amount of ALDH1A1 enrichment occurs in colon cancer [ 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…ALDH activity is high in cancer stem cells (CSC; aka tumor initiating cell) and is used to isolate these cells from a number of solid organ tumors [182][183][184][185][186]. Human tumors with increased ALDH1A1 positive cells measured at the protein level are associated with increased risk of recurrence in non-small cell lung cancer [187], enhanced invasiveness in nasopharyngeal carcinoma [188], and poor survival in bladder cancer [189], papillary thyroid carcinoma [190], head and neck cancer [191], esophageal SCC [192], colorectal can-cer [193], and breast cancer [194]. On the other hand, high ALDH1A1 levels predicted better outcomes in gastric cancer [195].…”
Section: Prognostic Value Of Altered Vitamin a Metabolismmentioning
confidence: 99%